Development of Interactive Multimedia-Based Learning Media in an Effort to Improve Student Learning Outcomes in Basic Automotive Technology Subjects Class X - Hidayatullah, Syarif; Waspodo, Muktiono; Herawati, Herawati (IJOEM Indonesian Journal of E-learning and Multimedia, 2024)
The research aims to develop interactive teaching materials that are integrated with LMS (e-learning) so that the learning process takes place effectively. This research is a type of Research and Development (R and D) research to improve student learning outcomes in the Basic Automotive Technology subject. The development method used in this research is to follow the ADDIE model. The subjects of this research are Learning Media, Learning Materials and Instructional Design. The next lesson is the students of Cibinong Mechanical Vocational School, namely class X TKR 1 as the experimental class. The results of the research show that the quality of the e-learning based interactive learning multimedia that was developed is in the very valid category (88.89), very good in one to one trials (91.07%), very good for small groups (91,93%) and very good for large groups (93,04%). Meanwhile, the tcount value is 6.701 and the ttable value at the 5% significance level is 2.051, so tcount>ttabel or 6.701>2.051, so ha is accepted and h0 is rejected. This means that there is a significant difference in the ability to understand material presented using media. So, it is concluded that interactive multimedia based on e-learning is feasible and effective and can improve student learning outcomes.